Moral Certainty and the Foundations of Morality - O'Hara, Neil (Springer International Publishing, 2018)
What lies at the foundation of our moral beliefs? If we dig down far enough do we find that our moral values have no ground at all to stand on, and so are apt to collapse upon serious philosophical investigation? This book seeks to answer these and related questions by positing an indubitable foundation for our moral beliefs - they arise from the phenomenon of 'primary recognition', and are fundamentally shaped by 'basic moral certainties'. Drawing on philosophers such as Ludwig Wittgenstein and Knud Ejler Løgstrup, this book draws together insights from both Analytic and Continental philosophy to provide a convincing new picture of our moral foundations. And it does so in a way that eschews moral conservativism and opens the way for a rich understanding of the variety and particularity of our human moral systems, while also keeping a significant place for those moral beliefs that occur universally, across cultures.